2019
DOI: 10.1080/22221751.2019.1677177
|View full text |Cite
|
Sign up to set email alerts
|

Molecular surveillance of antimicrobial resistance and transmission pattern of Mycobacterium leprae in Chinese leprosy patients

Abstract: Reports on antimicrobial resistance (AMR) of Mycobacterium leprae, relationship with bacteriological index (BI), and transmission in China are limited. We investigated the emergence of AMR mutations, the relationship between BI and AMR in complete, moderate and lack of BI decline cases, and molecular epidemiological features of AMR cases by enrolling 290 leprosy cases from four endemic provinces. Seven (2.41%), one (0.34%), five (1.72%), one (0.34%), and one (0.34%) strains had single mutations in folP1, rpoC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
(39 reference statements)
1
15
0
4
Order By: Relevance
“…[13,25,26] The prior use of FQ was reported in 18 studies (Table 4). [13,[24][25][26]29,[32][33][34][35][36][37][38][39][40][41][42][43][44] Mutations in gyrA (Tables 1, 4) Among the 18 substitutions described in GyrA, nine were inside and seven outside the QRDR, and two were inside the intein (Table 1). The A91 substitution was the most prevalent.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…[13,25,26] The prior use of FQ was reported in 18 studies (Table 4). [13,[24][25][26]29,[32][33][34][35][36][37][38][39][40][41][42][43][44] Mutations in gyrA (Tables 1, 4) Among the 18 substitutions described in GyrA, nine were inside and seven outside the QRDR, and two were inside the intein (Table 1). The A91 substitution was the most prevalent.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Only five studies reported substitutions in GyrB, using PCR sequencing or WGS. [3,29,[42][43][44] Among the 755 strains studied for GyrB, only nine (1.2%) harbored substitutions corresponding to three amino acid changes. Among these, two were inside the QRDR (D464N, also named D205N by two authors, and T503I) [3,29,44] and one was outside (V214G) [29,43] (Table 4).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Because of this Rifampicin resistance, fluoroquinolones became the preferred category of second-line drugs. Unfortunately, the stains of M. leprae with quinolone-resistance have been reported in several countries [ 16 ]. This might be because of the wide use of quinolones for treating numerous types of infections.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, all cases assessed through molecular biology were negative for drug resistance, corroborating the absolute effectiveness of the therapeutic scheme proposed by the Brazilian Ministry of Health 4 . However, some studies have indicated drug resistance to rifampicin, dapsone, and ofloxacin, also in cases of leprosy recurrence 12 - 14 , in addition to reporting mutations other than the traditional ones, such as nth (DNA repair), rpo , rpoC (rifampicin), gyrB (ofloxacin), and 23s rRNA (clarithromycin), but still having uncertain roles 13 . Reja et al 14 and Chauffour et al 15 affirmed that even cases of negative bacilloscopy can be targets of drug resistance, deserving even more attention during the follow-up period.…”
mentioning
confidence: 99%